Entrepreneurial intention among youths: The role of entrepreneurial education and passion - Zinhle Mhlongo; Sibusiso D. Ntshangase; Ikechukwu O. Ezeuduji (The Southern African Journal of Entrepreneurship and Small Business Management)
Background: Entrepreneurship contributes significantly to the enhancement and maintenance of a society’s economy by creating employment opportunities in both public and private sectors. South Africa faces significant economic challenges, with high youth unemployment rates necessitating innovative solutions to drive economic growth and job creation. Entrepreneurship, particularly supported through targeted education, offers a strategic pathway to address these issues.